Combining 'phonics' and 'whole language' approaches in teaching reading : a case study of Phenduka Literacy Project in an Alexandra school. - Murahwa, Sindisiwe (My University, 2009)
This research report is a case study, the aim of which is to describe and analyse the methods used by a non-profit organization in teaching Grade Seven (7) learners with reading difficulties in an Alexandra Township school, by using a combination of the whole language and phonics approaches. It involves Phenduka Literacy Project facilitators immersed in a two to three week literacy intervention with an average of 30- 35 Grade 7 learners at Dr Knak Primary School. The aim of the Phenduka programme is to improve learners’ levels of reading so that they can meet the demands of high school education. Data was collected by analysing the teaching material, carrying out semi-structured interviews with Phenduka facilitators, and observing the facilitators at work. The findings revealed that there is no one suitable method for teaching reading; rather, using an integrated approach would bear much fruits. It is envisaged that the findings of this study would enlighten teachers in disadvantaged communities in South Africa who face the same scenario of dealing with poor readers and using limited teaching/learning resources.
Keywords: Reading; Phonics approach; Whole language approach; Phenduka Literacy Project